Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 1 - Limits and Their Properties - 1.5 Exercises - Page 88: 19


Vertical asymptote at $x=-2$ and at $x=1.$

Work Step by Step

$f(x)=\dfrac{3}{x^2+x-2}=\dfrac{3}{(x+2)(x-1)}$ Vertical asymptotes occur when the denominator alone is $0\to$ $(x+2)(x-1)=0\to x=-2$ or $x=1.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.